2014
DOI: 10.1007/s12272-014-0351-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of C-glycosylation of luteolin on its antioxidant, anti-Alzheimer’s disease, anti-diabetic, and anti-inflammatory activities

Abstract: To investigate the effect of C-glycosylation at different positions of luteolin, the structure-activity relationships of luteolin and a pair of isomeric C-glycosylated derivatives orientin and isoorientin, were evaluated. We investigated the effects of C-glycosylation on the antioxidant, anti-Alzheimer's disease (AD), anti-diabetic and anti-inflammatory effects of luteolin and its two C-glycosides via in vitro assays of peroxynitrite (ONOO(-)), total reactive oxygen species (ROS), nitric oxide (NO), 1,1-diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 33 publications
1
50
1
Order By: Relevance
“…The natural flavonoid compounds, named the EA-CG extract, which contained five phytochemicals that are the major constituents of Maysin (i.e., Luteolin, Isoorientin, Rhamnosylisoorientin, Derhamnosylmaysin, and Maysin) in which those are may represents a potential anti-BACE1 phytochemicals as non-pharmacological alternatives or diet regimen that could prevent AD-like pathological symptoms by reducing soluble β-amyloid production and inhibiting amyloid plaque formation [20]. Compelling evidence support the premise likely effectiveness of natural flavonoids as Anti-AD in which one of flavonoid compound, Luteolin (include c-glycosylated derivatives) or Isoorientin, have shown its efficacy to prevent anti-Diabetic, anti-diabetic using diet induce cognitive deficit in obesity C57Bl/6 mice [35, 20] Liu et al reported that Luteolin exerted anti-AD effect such as impairment of spatial learning and memory capabilities, dysfunction of microvascular function, the intervene regional cerebral blood flow, result from Aβ (25–35) derived production of reactive oxygen species (ROS) using i.c.v. injection of aggregated Aβ (25–35) peptide in Male Kunming mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…The natural flavonoid compounds, named the EA-CG extract, which contained five phytochemicals that are the major constituents of Maysin (i.e., Luteolin, Isoorientin, Rhamnosylisoorientin, Derhamnosylmaysin, and Maysin) in which those are may represents a potential anti-BACE1 phytochemicals as non-pharmacological alternatives or diet regimen that could prevent AD-like pathological symptoms by reducing soluble β-amyloid production and inhibiting amyloid plaque formation [20]. Compelling evidence support the premise likely effectiveness of natural flavonoids as Anti-AD in which one of flavonoid compound, Luteolin (include c-glycosylated derivatives) or Isoorientin, have shown its efficacy to prevent anti-Diabetic, anti-diabetic using diet induce cognitive deficit in obesity C57Bl/6 mice [35, 20] Liu et al reported that Luteolin exerted anti-AD effect such as impairment of spatial learning and memory capabilities, dysfunction of microvascular function, the intervene regional cerebral blood flow, result from Aβ (25–35) derived production of reactive oxygen species (ROS) using i.c.v. injection of aggregated Aβ (25–35) peptide in Male Kunming mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…Orientin and isoorientin with 3 0 -OH group showed activities against HMGB1 and its receptors while vitexin and isovitexin without 3 0 -OH group showed no effect, indicating that the existence of 3 0 -OH group of flavone plays a pivotal role in anti-inflammatory activities (Yoo et al 2014). Furthermore, orientin with 8-C-glucoside was more active than isoorientin with 6-C-glucoside in anti-inflammatory activities both in vitro and in vivo (Choi et al 2014;Yoo et al 2014). Orientin, which has been used as an anti-inflammatory herb in China, regulates the key molecules involved in inflammation.…”
Section: C-glycosilationmentioning
confidence: 95%
“…Several studies have been focused on the link between diabetes mellitus (DM) and AD. In fact, insulin plays a major role in learning and memory processes, is also involved in neuromodulatory and neuroendocrine responses, as a consequence, the modification in the insulin pathway observed in diabetic patients is currently thought to be associated with cognitive impairment and dementia (Choi, Nurul Islam, Yousof Ali, Myeong Kim, et al, ). Moreover, several lines of evidence have demonstrated an increase in AChE activity in brains of diabetic rats (Sanchez‐Chavez & Salceda, ; Schmatz et al, ).…”
Section: Introductionmentioning
confidence: 99%